Enhanced growth and lipid productivity by living Chlorella sorokiniana immobilized in Ca-alginate beads. (1st January 2023) - Alfaro-Sayes, Daniel A; Amoah, Jerome; Rachmadona, Nova; Hama, Shinji; Hasunuma, Tomohisa; Kondo, Akihiko; Ogino, Chiaki
Abstract: The bottleneck for the production of biofuels from microalgae consists on costly harvesting processes and low lipid production, immobilization technology could play a part on making the production of biofuels more feasible. The aim of this study was to evaluate the effect of alginate immobilization on the growth and lipid productivity of the microalgae Chlorella sorokiniana, so far, the main focus of immobilization technology has been its use for wastewater treatment and nutrient removal from effluents. The microalgae Chlorella sorokiniana was cultured in both free and immobilized forms under optimal autotrophic growth conditions. Microalgae were immobilized in calcium alginate beads generated by mixing algal cells with a sodium alginate solution, followed by extrusion into a CaCl2 solution. The results obtained in this study showed that the growth of the microalgae immobilized in alginate beads, was enhanced and achieved a dry cell weight 1.4-fold higher than that of a free cell culture, a higher light transmittance was also achieved in the alginate immobilized culture, and the lipid productivity was increased from 54.21 ± 2.48 mg l −1 d in the free cell culture to 82.22 ± 8.48 mg l −1 d in the immobilized culture. These results demonstrate the effectiveness of immobilization technology for promoting growth and lipid productivity in the microalgae Chlorella sorokiniana .